EKSPEDISI EKSPLORASI KEBERAGAMAN BUDAYA NUSANTARA SEBAGAI RUANG PENGUATAN CIVIC ENGAGEMENT - Miranda Siregar; Asep Mahpudz; Fitria, Ratna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of the Nusantara cultural diversity exploration expedition in strengthening civic engagement among nature-lover organization members through a comparative study of Perhimpunan Penempuh Rimba dan Pendaki Gunung Wanadri and MAPACH UPI. This study employed a descriptive qualitative approach with purposively selected informants. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data display, and conclusion drawing using source and technique triangulation. The findings show that expeditions serve as spaces for civic engagement reflected in social engagement, volunteerism engagement, and cultural engagement. Differences in organizational characteristics indicate that Wanadri develops civic engagement through pioneering, exploration, humanity, and environmental orientations, while MAPACH UPI integrates civic engagement through an academic approach based on the Tri Dharma of Higher Education.